Large tensile-strain-induced monoclinic MB phase in BiFeO3 epitaxial thin films on a PrScO3 substrate - Chen, Zuhuang (2014)
Crystal and domain structures, and ferroelectric properties of tensile-strained BiFeO3 epitaxial films grown on orthorhombic (110)o PrScO3 substrates were investigated. All films possess a MB-type monoclinic structure with 109° stripe domains oriented along the [1¯10]o direction. For films thicknesses less than ∼40 nm, the presence of well-ordered domains is proved by the detection of satellite peaks in synchrotron x-ray diffraction studies. For thicker films, only the Bragg reflections from tilted domains were detected. This is attributed to the broader domain size distribution in thicker films. Using planar electrodes, the in-plane polarization of the MB phase is determined to be ∼85 μC/cm2, which is much larger than that of compressive-strained BiFeO3 films. Our results further reveal that the substrate monoclinic distortion plays an important role in determining the stripe domain formation of the rhombohedral ferroic epitaxial thin films, which sheds light on the problem of understanding elastic domain structure evolution in many other functional oxide thin films as well.